HUBUNGAN ANTARA KECERDASAN EMOSIONAL DENGAN KEMAMPUAN KOMUNIKASI MATEMATIS PESERTA DIDIK KELAS VIII SMP NEGERI SE-KECAMATAN AMPENAN TAHUN AJARAN 2019/2020 - Yaumi Oktari; Azmi, Syahrul; Kurniati, Nani (Jurnal Ilmiah Pendidikan Indonesia, 2021)
This study aim is to determine the relationship between emotional quotient and mathematical communication capability of students in grade VIII Junior High School among Ampenan District academic year 2019/2020 . The type of study used is quantitative research with ex post facto method. The population in this study were all students in grade VIII among junior high schools in Ampenan Subdistrict viz. SMP Negeri 3 Mataram, SMP Negeri 10 Mataram, SMP Negeri 18 Mataram, and SMP Negeri 24 Mataram whilethe sample are students on grade VIII-A and VIII-C in SMP Negeri 10 Mataram and students on grade VIII-A in SMP Negeri 24 Mataram. The data obtained by questionnaire method for emotional quotient data and test methods for data mathematical communication capability written. The hypothesis testing method used is the Spearman rank correlation by comparing the calculated z values ??with z tables. The results of this study indicate that the level of emotional quotientis 87% of students with moderate emotional quotient category and 13% of students with high emotional quotient category. The level of mathematical communication capability of students is 23% low category, 65% moderate category, and 12% high category. By comparing the z count value of 0.23 and z table of 1.96, it was concluded that there was no significant relationship between emotional quotient and mathematical communication capability of students in grade VIII Junior High School among Ampenan District academic year 2019/2020.